2020
DOI: 10.1021/acscatal.0c00954
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hydrogen Poisoning by Electrostatically Polar MgO Support for Low-Pressure NH3 Synthesis at a High Rate over the Ru Catalyst

Abstract: Vulcan carbon was pre-treated at 850 o C at a ramp rate of 5 o C/min and maintained for 24 hours under 5% H2 in Ar. Cs-Ru modified MgO and AC preparationTypically, Ru3(CO)12 was dispersed in THF for 2 hours under sonication. The mixture was then transferred to the MgO or activated carbon (AC) and allowed to sonicate at ambient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 41 publications
3
92
0
Order By: Relevance
“…Such a difference in the product is likely due to the special preferential orientation and specific electronic properties of the well-defined MgO(111) support. This polar surface has been proposed to have unique catalytic properties, 48,49 which rises our interests to study the reaction mechanism with combined IR, UV-Vis, isotope labeling and solid-state NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Such a difference in the product is likely due to the special preferential orientation and specific electronic properties of the well-defined MgO(111) support. This polar surface has been proposed to have unique catalytic properties, 48,49 which rises our interests to study the reaction mechanism with combined IR, UV-Vis, isotope labeling and solid-state NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al reported that hydrogen poisoning of the Ru surface was suppressed by simple replacement of the polycrystalline MgO(110) or (100) with polar MgO(111). 10 Comparison of the NH 3 synthesis rate revealed that Ru/MgO(111) has a much higher NH 3 synthesis rate than that of Ru/MgO(110) or (100), although the N 2 reaction order was almost identical (Ru/ MgO(111): 0.9, Ru/MgO(110): 0.9, Ru/MgO(100): 0.8). In addition, the H 2 reaction order became a positive value (0.6) over Ru/MgO(111) from negative values over other MgO surfaces (Ru/MgO(110): À0.2, Ru/MgO(100): À0.5).…”
Section: Suppression Of Hydrogen Poisoningmentioning
confidence: 97%
“…Hydrogen migration plays an important role in various catalyses such as hydrogenation-dehydrogenation of hydrocarbon, 1-5 CO 2 reduction [6][7][8][9] and NH 3 synthesis. [10][11][12][13][14][15][16][17] However, the utilisation of hydrogen migration is not limited to catalysis. It is also fundamentally important for catalyst preparation, 18,19 hydrogen storage, 20,21 fuel cells and sensors.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] We thus reasoned that using ultrathin Mg(OH) 2 (0001) nanosheets as template should allow the gram-scale synthesis of ultrathin MgO(111) nanosheets.M gO is especially interesting because it is ak ey support in heterogeneous catalysis due to its basic properties. [10] Thepolar MgO(111) surface with intrinsic perpendicular electrostatic field is proposed to have unique catalytic properties, [11] but remains challenging to prepare due to its thermodynamic instability and high surface energy. [12] Apart from physical or chemical evaporation-deposition methods that produces thin films under ultrahigh vacuum, [13] synthetic methods to prepare MgO(111) as af ree standing solid are limited and lead to polycrystalline nanosheets or octahedral microcrystals.…”
Section: Introductionmentioning
confidence: 99%